2005
DOI: 10.1094/cc-82-0488
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between NIR Spectra and RVA Parameters During Wheat Germination

Abstract: Cereal Chem. 82(5):488-493The process of germination in six different wheat cultivars was monitored using NIR spectroscopy and the Rapid Visco Analyser (RVA) method. Near-infrared spectra provided insight into both chemical and physical changes that occur in the seed, in particular mobilization processes involving carbohydrates. RVA curves also contain physical and chemical information and can be interpreted as physicochemical spectra. The process of germination was followed sensitively through the RVA curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
(51 reference statements)
6
14
0
Order By: Relevance
“…For example, peak viscosity and final viscosity of GBR were 1217 cP and 203 cP, respectively. Similar trends were reported by Juhasz et al (2005) for wheat (Triticum aestivum L.) seed, and by Xu et al (2012) for brown rice flour. The substantial decrease in pasting viscosity was mainly due to starch and protein degradation occurring during germination.…”
Section: Pasting Viscositysupporting
confidence: 81%
“…For example, peak viscosity and final viscosity of GBR were 1217 cP and 203 cP, respectively. Similar trends were reported by Juhasz et al (2005) for wheat (Triticum aestivum L.) seed, and by Xu et al (2012) for brown rice flour. The substantial decrease in pasting viscosity was mainly due to starch and protein degradation occurring during germination.…”
Section: Pasting Viscositysupporting
confidence: 81%
“…Several factors might influence this region and can be associated with the proportion of small starch granules (shown to positively correlate with peak viscosity and final viscosity but negatively with initial pasting time), amylose to amylopectin ratio, the relative diameter of large starch granules, lipid content and other pasting characteristics. Similar results were reported by other authors (Goode et al, 2005a,b;Juhasz et al, 2005;Juhasz and Salgo, 2008;Li and Yeh, 2001;Meadows, 2002;Meadows and Barton, 2002;Xie et al, 2005).…”
Section: Rva Profilesupporting
confidence: 92%
“…Without the use of baseline and second derivatives as pre-processing of the RVA profiles of barley flour and malt samples, relevant information related to the pasting properties of the sample can be lost. Similar results were reported by other authors (Juhasz et al, 2005;Juhasz and Salgo, 2008;Meadows, 2002;Meadows and Barton, 2002). These authors reported that the use of the first derivatives to the RVA profile improved the information generated by the instrument.…”
Section: Rva Profilesupporting
confidence: 89%
See 1 more Smart Citation
“…NIRS has applications in the agricultural industry as well as many other fields, including food science, biological and biomedical areas, and the pharmaceutical, textile, cosmetic, and chemical industries [7]. Recently, NIRS is applied to discriminate normal seed in radish [8] and wheat [9]. Moreover, this technique has been applied for nondestructive classification of viable and empty seeds of Pinus plata seeds [10] and Raphanus sativus seeds [11].…”
Section: Introductionmentioning
confidence: 99%